Nursing care in women's mental health during the pregnancy-puerperal cycle (Research, Society and Development, 2022)
Introduction: The pregnancy-puerperal cycle is characterized by presenting a set of physiological, psychic, hormonal and social alterations that permeate an increased risk for emotional distress and it is up to the health professional to be attentive to the mental and emotional condition of the woman since he provides care to her throughout this period. Aim: To analyze nursing care in women's mental health during the pregnancy-puerperal cycle. Methodology: This is an integrative review, starting from the guide question "How will nursing care contribute to the mental health of women during pregnancy, childbirth and puerperium?" The following databases were used: LILACS, SciELO and BDENF, using the descriptors: women's health; mental health; pregnancy; childbirth; puerperium and nursing. The searches were carried out in September and October 2021, and included articles published between 2016 and 2021 in the Portuguese, English or Spanish. Results: The final sample of this review consisted of eleven scientific articles, which show that nursing care, being performed in an integral way, can prevent mental disorders that can directly affect women in the gestational, childbirth and puerperal period, since they are periods of vulnerability and transformation. Conclusion: There is a great failure of the mental health approach in the pregnancy-puerperal period in women. It is noted that nursing care in full form, especially in prenatal care, can avoid complications in the mental state of both women and children.